The musical traditions of Northern Ireland and its diaspora : community and conflict - Cooper, David, 1956- (Ashgate popular and folk music series., 2009)
Northern Ireland remains a divided community in which traditional culture, in all its manifestations, is widely understood as a marker of religious affiliation and ethnic identity. Since the outbreak of the most recent 'troubles' around 1968, the borders between the communities have often been marked by music. With the increasing espousal of a discrete Ulster Scots tradition since the signing of the Belfast (or 'Good Friday') Agreement in 1998, the characteristics of the traditional music performed in Northern Ireland, and the place of Protestant musicians within popular Irish culture, clearly.